Integration of the history of science in China's geography textbooks: a comparative analysis of current versions of eight junior high school textbooks - Cheng, Jian; Lu, Yihua; Wang, Kun; Zhang, Mingcan; Chen, Shi (Frontiers in Education, 2025)
IntroductionThe presentation of the history of science (HOS) in textbooks plays a vital role in fostering scientific literacy, as its selection and pedagogical implementation directly influence the quality of student learning.MethodsThis study applied a revised analytical framework for HOS, which encompasses four themes and ten dimensions: thematic content, presentation modes, pedagogical activities, and value orientations. Based on this framework, a comparative analysis was conducted across eight current versions of junior high school geography textbooks in China.ResultsThe analysis revealed that (1) the overall quantity of HOS content is limited across textbooks. Within thematic content, “significant events and expeditions” are most common, whereas “geographers and explorers” are least represented, with varied emphases on sources of HOS. (2) In terms of presentation, HOS is predominantly delivered through text-image integration in the “Main Body” and “Supplementary Reading” sections, though unevenly distributed. Integration depth is primarily intrinsic and supplementary, showing exploratory potential. (3) Pedagogical activities are mainly optional, with notable variation in cognitive levels across versions: some emphasize foundational tasks, while others stress deepening activities. Guided reading and inquiry-based discussion dominate, though overall diversity of activities is lacking. (4) The epistemological and cultural orientations are relatively monolithic, focusing on discipline-specific knowledge over humanistic or philosophical perspectives. Attitudinal orientations are mostly neutral or positive.DiscussionThese findings indicate that while HOS is included in junior high school geography textbooks, its representation remains limited and uneven in both content and pedagogy. Enhancing the diversity of HOS content, presentation, and learning activities, as well as broadening its value orientations, may contribute to more comprehensive cultivation of scientific literacy.